PENGARUH EFEKTIVITAS PROMOSI MEDIA SOSIAL DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN: Studi Iklan Facebook Ads Pada Pempek Dok Sikam Blitar - Yufi Priyo Sutanto; Sunan Trioko (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
The use of social media in Indonesia is growing rapidly. Effective marketing through social media influences buying interest. Consumer buying interest also be influenced by product quality. The purpose of this study is to analyze the effectiveness of social media promotion using Facebook ads and the quality of this product affects consumer buying interest with the research object of Pempek Dok Sikam. The research method used is descriptive quantitative research that measures the strength of the relationship between two or more variables. Partial testing shows the effectiveness of social media promotion (X1) has a significant effect on buying interest. Likewise, product quality (X2) has a significant effect on buying interest. Simultaneous testing results show that the two independent variables, namely the effectiveness of social media promotion (X1) and product quality (X2), together (simultaneously) have a significant effect on buying interest (Y). The test results of the coefficient of determination presented show that the variables measured by the effectiveness and quality of the product that can be explained by the purchase interest variable is 46.9%, while the remaining 53.1% is explained by other variables not examined in this study.